2021
DOI: 10.3390/su13041847
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Distributed System of e-Vehicle Charging Stations Based on Pumps as Turbine to Support Sustainable Micromobility

Abstract: Recent statistics shows that CO2 emissions from road transport have been increasing. In addition, the paradigm of “more electric vehicles” does not seem to be positive from the environmental point of view. In fact, assuming the current energy mix system, studies focusing on Life Cycle Assessment and Well-To-Wheels analysis demonstrate that electric vehicles are less eco-friendly than traditional internal combustion-based engines. Then, it is mandatory to shift toward renewable energy sources to produce electri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…One study suggested that traditional delivery vehicles used for mail or package delivery have too much impact on CO2 emissions. Some studies shared some statistical results that road transport increases CO2 emissions [24]. Trucks and derivative vehicles used in the package or mail transport system are responsible for 24% of greenhouse gas emissions [19,20].…”
Section: Introductionmentioning
confidence: 90%
“…One study suggested that traditional delivery vehicles used for mail or package delivery have too much impact on CO2 emissions. Some studies shared some statistical results that road transport increases CO2 emissions [24]. Trucks and derivative vehicles used in the package or mail transport system are responsible for 24% of greenhouse gas emissions [19,20].…”
Section: Introductionmentioning
confidence: 90%
“…Problems mainly related to the demand management are explored in [17]. Other problems are related to vehicles energies consumption ( [30,31]) and transit and dynamic optimal travel strategies simulation (i.e., ref. [32][33][34][35]).…”
Section: Decision Support System Platformmentioning
confidence: 99%
“…The research results of centrifugal pumps are relatively mature and systematic, while those of PAT are relatively lacking. With the intensification of global climate problems in recent years, PAT has become one of the research hotspots in the field of hydraulic machinery and energy-saving energy storage (Balacco et al, 2021;Cao et al, 2021;El-Emam et al, 2022).…”
Section: Introductionmentioning
confidence: 99%